Highly anisotropic Cu oblate ellipsoids incorporated polymer composites with excellent performance for broadband electromagnetic interference shielding - Lee, Seung Hwan; Yu, Seunggun; Shahzad, Faisal; Hong, Jun Pyo; Kim, Woo Nyon; Park, Cheolmin; Hong, Soon Man; Koo, Chong Min (ELSEVIER SCI LTD, 2017)
In this study, highly anisotropic Cu oblate ellipsoids incorporated polymer composites were prepared that revealed excellent broadband electromagnetic shielding effectiveness of 80.0 to 62.1 dB at a frequency region between 300.0 KHz and 12.0 GHz, at low Cu contents. Cu-coated hollow polymer beads were fabricated through electroless plating of Cu on the polymer hollow beads. The hollow polymer beads were prepared through thermal expansion of acrylonitrile-based polymer beads containing a blowing agent. These beads were capable of incorporating highly anisotropic 2-dimensional (2D) Cu oblate ellipsoids into polymer composite through simple compression molding process. The resulting broadband electromagnetic shielding performance attributes to a low percolation behavior of the composites due to high anisotropy of the conductive Cu filler and their multilayered structure in the composites. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: GRAPHENE; NANOCOMPOSITES; CONDUCTIVITY; FILMS